The Validity Analysis of the STEM-Based Biotechnology E-Book to Enhance Students’ Creative Thinking Ability and Skills in Producing Innovative Works - Nor Indriyanti Nor Indriyanti (Universitas Sulawesi Barat, 2025)
This study aims to develop and validate a STEM-based Biotechnology E-Book designed to enhance students’ creative thinking abilities and skills in producing innovative works. The research method employed was Research and Development (R&D), consisting of stages including needs analysis, design, product development, and expert validation. The instrument used was a validation sheet covering aspects of content, language, presentation, and graphics. Data were analyzed using descriptive percentage techniques by calculating the Mean Score Percentage (MSP) and interpreting the results according to validity criteria. The findings indicate that the STEM-based Biotechnology E-Book meets the “very good” category in nearly all validated aspects. The content aspect achieved an average MSP of 96.48%, the language aspect 98.21%, the presentation aspect 95.3%, and the graphic aspect 96.4%. All indicators fell within the valid category, with only a few components rated as “good.” These results affirm that the developed e-book possesses material quality aligned with the Learning Outcomes (CPL) and Course Learning Outcomes (CPMK), employs appropriate and motivational language, provides systematic presentation, and features visually appealing and proportional graphics. Based on these findings, it can be concluded that the developed STEM-based Biotechnology E-Book is feasible to be used as an alternative learning medium in the Biotechnology course. This product has the potential to support the enhancement of students’ creative thinking skills and innovative abilities. Further research will be conducted to examine the effectiveness and practicality of the product more broadly in testing students’ creative thinking and innovative skills.